2021
DOI: 10.3390/socsci10010008
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Behavior of SMEs and Characteristics of the Managers of Northwest Mexico

Abstract: The objective of this study is to determine the difference in the entrepreneurial behavior of companies based on the demographic characteristics of their manager or leader. To comply with the above, a quantitative, transversal, and non-experimental research study was carried out, which consisted in applying an instrument to 262 managers of small and medium enterprises (SMEs) in a northern city in Mexico. The collected information was analyzed in the software SPSS, version 26, with statistical testing by the Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…This is recurrent within certain sectors of Brazilian SMEs (Cassol et al, 2019). In the context of early-stage post-IPO American startups, the phenomenon remains unchanged, and two reasons for this are the We can also infer that the idiosyncrasies that make up the organizational structure of SMEs (Hotho et al, 2012;Jiménez et al, 2021;Thomas & Wood, 2015), generally characterized by family management with limited formal education and intuitive administrative principles, hinder the adaptation and application of this new knowledge to the business. For Finally, when analyzing the practices related to innovation, we are looking at the updating of services that have been implemented and have yielded results for the hotels.…”
Section: Theoretical and Managerial Discussionmentioning
confidence: 99%
“…This is recurrent within certain sectors of Brazilian SMEs (Cassol et al, 2019). In the context of early-stage post-IPO American startups, the phenomenon remains unchanged, and two reasons for this are the We can also infer that the idiosyncrasies that make up the organizational structure of SMEs (Hotho et al, 2012;Jiménez et al, 2021;Thomas & Wood, 2015), generally characterized by family management with limited formal education and intuitive administrative principles, hinder the adaptation and application of this new knowledge to the business. For Finally, when analyzing the practices related to innovation, we are looking at the updating of services that have been implemented and have yielded results for the hotels.…”
Section: Theoretical and Managerial Discussionmentioning
confidence: 99%
“…A study on young managers suggests that certain leadership behaviors may be enhanced or diminished depending on the leader's age (Buengeler et al, 2016). It has also been found that the entrepreneurial behavior in organizations varies depending on the age and educational level of their managers (Jiménez et al, 2021). The existing evidence motivates to explore the desired objective of the present study.…”
Section: Introductionmentioning
confidence: 89%
“…For this reason, we decided to direct the study’s data collection efforts toward suitable and sufficient MSMEs through convenience sampling. Similar studies have analyzed the characteristics and development of organizations throughout their life cycle using a non-probability quota sample (Adizes et al, 2017 ; Ochoa Jiménez et al, 2021 ; Tam & Gray, 2016b ). We acknowledge the criticism of this technique for its limited generalization (Jager et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%